On spectra of microwave oscillations of the 0-degree domain wall in a cubic ferromagnetic - Vakhitov, R.M.; Sergeyev, E.I. (Functional Materials, 2006)
A cubic ferromagnetic with uniaxial anisotropy induced along the [111] axis is considered that contains a defect as a slab-like magnetic inclusion. It is assumed that a magnetic inhomogeneity is localized on that inclusion, the model representation of the inhomogeneity corresponding to the magnetization distribution in a zero-degree domain wall. The microwave excitation of the 0-degree domain wall have been investigated numerically and the features of their spectra have been considered depending on the sample material parameters and the defect characteristics.